Profiles of Teacher Professional Identity Among Student Teachers and Its Association With Mental Health - Zhao, Shunying; Dong, Yang; Luo, Jian (Frontiers in Public Health, 2022)
In recent years, studies exploring the link between teacher professional identity and mental health are increasing. However, such research using latent profile analysis is still scarce. The aim of this study was to examine the heterogeneity of a sample of 923 student teachers’ professional identity and its association with mental health (i.e., psychological well-being and anxiety). By using latent profile analysis, four different profiles were identified: 1) low professional identity (LPI, 5.1%), 2) moderate professional identity (MPI, 42.7%), 3) high occupational values (HOV, 12%), and 4) high professional identity (HPI, 40.2%). The results demonstrated that psychological well-being and anxiety were significantly different across the four profiles. In addition, the anxiety of HOV group was not significantly with LPI and MPI groups. This study indicated that student teachers in different groups may have different mental health status.